Analyzing exosomal miRNA profiles in tetralogy of fallot fetuses’ amniotic fluid - Hainan Yang; Yadan Li; Qiuyue Chen; Shangqing Li; Yiru Yang; Guorong Lyu (Scientific Reports)
Abstract Amniotic fluid (AF)-derived exosomal miRNA have been explored as potential contributors to the pathogenesis of Tetralogy of Fallot (TOF). This study aimed to investigate the expression profiles of AF-derived exosomal miRNAs and their potential contribution to TOF development. Exosomes were isolated from AF samples obtained from pregnant women carrying fetuses diagnosed with TOF. AF-derived exosomal miRNAs expression profiles were generated using the Agilent human miRNA Array V21.0, comparing 5 TOF samples with 5 healthy controls. Differential expression analysis identified 257 significantly dysregulated miRNAs in the TOF group. KEGG pathway enrichment analysis revealed that the predicted targets of these differentially expressed miRNAs were enriched in pathways associated with congenital disorders. Notably, 25 of these miRNAs were previously reported to be regulated by both Notch and Wnt signaling pathways, which are critical to heart development. Further investigation using mouse embryonal carcinoma P19 cells revealed that miR-10a-5p overexpression inhibited cardiomyogenic differentiation, as evidenced by the suppression of cardiomyocyte marker genes like TBX5. A dual-luciferase reporter assay confirmed TBX5 as a direct target of miR-10a-5p, suggesting a regulatory mechanism involving their interaction. In summary, our study demonstrates that miR-10a-5p may contribute to the pathogenesis of TOF by impairing cardiomyocyte differentiation through direct targeting of TBX5. These findings enhance our understanding of TOF and its molecular underpinnings.